The urban unbanked in Mexico and the United States - John, Patrick (Policy research working paper, 2006)
"This paper examines the ways in which lower-income households obtain basic financial services in urban communities in Mexico and the United States. And it discusses the efforts that private sector and government organizations are making to lower the cost or improve the quality of those services. The paper summarizes available information on these issues and assesses the rationale and challenges facing the strategies that both countries are using to improve the financial services available to lower-income households, giving particular attention to "unbanked" households, meaning households that do not have deposit accounts with any regulated deposit-taking institution, and also to lower-income households in large urban areas. In comparing the experiences of the two countries, the paper reviews the extent to which lower-income households are unbanked, their use of non-bank financial services, and strategies for improving financial services to the unbanked. The underlying differences between the countries' typical household incomes-national income per capita in Mexico in 2002 was US